Fetal Monitoring in Open Fetal Surgery - Kemal Tolga Saracoglu (Global Journal of Anesthesiology - Peertechz Publications, 2015)
Open surgery and fetoscopic surgery are of the safest procedures, whilst the ex-utero intrapartum treatment (EXIT) procedure has lost its significance as a result of the severe complications experienced both by the mother and the fetus. While uteroplacental circulation maintains, the EXIT is performed before delivery. The fetus is to be delivered at the conclusion of the case. A neonatal resuscitation area and two operating rooms are needed. Significant uterine relaxation is required for open midge station surgery. The risk for rapid bleeding and hemodynamic instability are the common accompanying parts of this procedure. It still continues to be a process done in certain centers not only in United States but also in Europe [1].